The sound of architecture: Music in architectural design - Oretorp, Kristin (My University, 2022)
Throughout history, there have been analogies between Architecure and Music as creative and artistic practises. Analogies in the methods of conducting the creative design process. Analogies in the vocabulary used to describe how we create and experience music and architecture. Analogies in how we use notation as a means of describing our artistic intentions. In this thesis, these analogies are explored using the shared vocabulary as framework and layered mapping as working method. The aim is to explore how the shared vocabulary could be used as a framework within which architecture could be analysed and experienced through a musical lens, and how such a framework could be a starting point for developing a method where music can be integrated in the architectural design process. The site for the final design proposal is the Gothenburg Opera, a building with a multitude of features and sequencial shifts. The existing building has been mapped using a framework including five terms from the shared vocabulary of both music and architecture. The map has been the basis of continuous conversations within an established collaboration with Daniel Berg and Tobias Granmo, musicians and professors at the Academy of Music and Drama. Within this collaboration, one piece of music has been chosen for each sequence in the mapping. The music in combination with the mapping of the Gothenburg Opera has been the foundation in the design of an extension - The Little Opera.
Keywords: Rythm; Harmony; Volume; Ornamentation; Movement